Applying the social ecological framework to enhance wellness for student veterans. Issue 7 (3rd October 2022) - Morris, Phillip A.; Barker, Lisa; Monar, Astrid
Abstract: Objective To increase campus-wide wellness for student service members/veterans (SSM/Vs), student services professionals, healthcare providers, and faculty collaborated to implement the Social Ecological Framework (SEF) over a three-year project. Participants One thousand six hundred and seventy eight SSM/Vs enrolled at a medium-sized doctoral granting institution with high-research activity (R2). SSM/Vs were directly and indirectly impacted through a series of initiatives, including stigma reduction efforts, wellness promotion, faculty training, therapeutic services, and peer-advising. Methods Data collection included student success measures such as retention, student satisfaction/feedback, peer-advising meetings, psychotherapy sessions, TBI screenings, and growth measures from a mental health stigma scale. Results A significant increase in therapy sessions conducted at the Wellness Center, increased faculty trainings, new and strengthened partnerships, and an increase in SSM/V retention. Conclusions Results suggest that collaborative efforts applying the SEF can create improved educational conditions and outcomes for SSM/Vs. A review of SSM/V wellness literature and suggestions for other campuses are offered.